Histamine contents in Georgian qvevri wines with different wine faults (Wine Studies, 2024)
Seventy-two qvevri wine samples from different regions of Georgia were studied for histamine and first ever results for Georgian qvevri wines were presented. Organoleptic analysis detected several wine faults that gave the possibility to search for correlation between elevated histamine contents and wine faults. Histamine content of the samples is presented according to the groups which were composed according to the tasting results and lactic/malic acid measurements. The influence of the activity of lactic acid bacteria (LAB) on the formation of histamine was clearly confirmed in the category of qvevri wines where Malolactic Fermentation (MLF) did not take place. Wines produced according to spontaneous MLF had higher histamine contents than the wines where MLF was induced by inoculated commercial LAB species but included low concentrations as well. This underlined the unpredictability to forecast histamine production by spontaneous MLF and confirmed the benefit of using commercial Oenococcus oeni LAB species for lower histamine accumulation in wines. Other categories represented wines where spontaneous MLF took place and contained one or more wine faults. Wines with “tourne” and lactic smell with elevated volatile acidity (VA) had higher levels of histamine but wines with mice flavour did not so. These results suggest that the ability of bacteria to cause some of the wine faults: “tourne”, lactic smell + elevated VA, might be associated with their ability to produce higher amounts of histamine as well.
Keywords: Biogenic amines; wine faults; lactic acid bacteria; malolactic fermentation